Rail Transportation 2002
DOI: 10.1115/imece2002-39623
|View full text |Cite
|
Sign up to set email alerts
|

Developing Guidelines for Crashworthiness of Light Rail Vehicles in Mixed Fleet Operations

Abstract: As new passenger rail cars are introduced into existing rail fleets, the potential structural for incompatibility between cars in a collision is a safety concern. Crush damage that occurs when dissimilar strength vehicles collide is concentrated in the weaker vehicle. In a serious collision the deformation of the weaker vehicle could be sufficiently large to intrude into the occupied volume of the operator or passenger compartments. As a result, the strength incompatibility has the potential for increased risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…In a contrary fashion, some structures may harden at such a high rate once collapse begins that minimal energy is absorbed and deceleration of the light rail vehicle occupants is severe [8]. Figure 2 illustrates the concepts of structural softening and hardening [8]. Application of a prescriptive metric such as th static strength without specification of the de behavior is a shortcoming of this approach.…”
Section: Discussion Distinction Between Cem and Static Strengthmentioning
confidence: 94%
See 3 more Smart Citations
“…In a contrary fashion, some structures may harden at such a high rate once collapse begins that minimal energy is absorbed and deceleration of the light rail vehicle occupants is severe [8]. Figure 2 illustrates the concepts of structural softening and hardening [8]. Application of a prescriptive metric such as th static strength without specification of the de behavior is a shortcoming of this approach.…”
Section: Discussion Distinction Between Cem and Static Strengthmentioning
confidence: 94%
“…Structural behavior can be unpredictable and in some cases the crush load after initial collapse drops in magnitude, potentially leading to rapid structural collapse of the operator compartment or the passenger compartment. In a contrary fashion, some structures may harden at such a high rate once collapse begins that minimal energy is absorbed and deceleration of the light rail vehicle occupants is severe [8]. Figure 2 illustrates the concepts of structural softening and hardening [8].…”
Section: Discussion Distinction Between Cem and Static Strengthmentioning
confidence: 95%
See 2 more Smart Citations
“…Due to the large difference in shape between trams and passenger vehicles, some scholars have considered introducing the concept of collision compatibility into the study of collision safety between urban rail vehicles and passenger vehicles. Steven W. Kirkpatrick et al found that the mismatch of tram quality, shape and strength will bring risks to trams and passengers by studying the collision accidents of different types of trams [8] . Robert T. Bocchieri, combined with the research results of Steven W. Kirkpatrick, studied the front-end protection energy absorption device of the tram and found that adjusting the contour of the energy absorption device can effectively improve the safety of tram operation [9] .…”
Section: Introductionmentioning
confidence: 99%